AUTOMATIC GARBAGE ISOLATOR - Sophia, Dr.P.Eben (International Journal of Psychosocial Rehabilitation, 2020)
Rapid population growth has also made to an increase with the quantity of garbage which is produced in our daily days. This leads to increases in the creation of waste due to repeated development in the industrialization and urbanization have become a critical issue for local and national governments. It also poses a critical challenge for local authorities to handle the waste which is being collected as landfill in every field. Meticulous measures need to be taken when segregating and transporting waste to make sure that the minimal risk to the surrounding and human health. The correct division of waste takes the actual economic value of the garbage to the limelight. The traditional method which is used in Indian waste segregation is through time-consuming rag pickers that can adversely affect the health of human who are exposed to such wastes. Here we suggest the use of an affordable Auto waste isolator (AWI) which is also an easy to use a solution for household waste separation. It is planned to seperate the waste into three groups’ metallic wastes, dry waste, and wet waste. The system uses a moisture sensor will segregate wet and dry waste, and an inductive proximity sensor to detect metallic waste, and a GSM is used to transmit user information about the separated garbage data. From experimental reports it is evident that waste segregation using Automated Garbage Isolator was successful.